Analisis Respon Hidrologi dan Simulasi Teknik Konservasi Tanah dan Air Sub DAS Cimanuk Hulu: Analysis of Hydrology Response and Simulation of Soil and Water Conservation Enginerring in Upstream Cimanuk Sub Watershed - Gilang Munggaran; Yayat Hidayat; Surya Darma Tarigan; Dwi Putro Tejo Baskoro (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Cimanuk Watershed is a priority catchment in West Java Province. The objective of the study is to analyze various land-use scenarios to improve base flow and lateral flow. The analysis use SWAT Hydrology model. The study showed that the model has a good performance in predicting flow discharge produced NSE 0.56 (satisfactorily) and R2 0.70. There are four scenarios to be analyzed. The best base flow and lateral flow analyses are from the first scenario with soil and water conservation techniques. The scenario resulted in the river regime coefficient by 78 (moderate), reduce direct runoff by 40.76% and increase lateral by 536.95 mm. Keywords: Baseflow, landuse, lateral flow, soil, and water conservation techniques, SWAT model